2005
DOI: 10.1016/j.joca.2005.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Medial and lateral osteoarthritis of the knee is related to variations of hip and pelvic anatomy

Abstract: Our findings suggest that occurrence of medial or lateral OA has a biomechanical background originating from pelvis and hip anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 16 publications
4
36
2
Order By: Relevance
“…We previously found that these patients had a broader pelvis than controls and medial OA patients. 27 Lateral OA was also associated with a steeper angle of the femoral neck (coxa valga) on the AP view, which could be due to more anteversion or increased external femoral rotation as observed in this dynamic study. This femoral deformity, which might compensate for a wider pelvis, might have developed during growth because of muscular imbalance or acetabular dysplasia.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…We previously found that these patients had a broader pelvis than controls and medial OA patients. 27 Lateral OA was also associated with a steeper angle of the femoral neck (coxa valga) on the AP view, which could be due to more anteversion or increased external femoral rotation as observed in this dynamic study. This femoral deformity, which might compensate for a wider pelvis, might have developed during growth because of muscular imbalance or acetabular dysplasia.…”
Section: Discussionsupporting
confidence: 58%
“…Presence of hip disease may be another reason. In a previous study of lateral knee OA patients, 27 we observed that as many as half of the cases also had OA of the hip, which will impair hip extension.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations